SPOTLIGHT ON PERSONAL ACCOUNTING. - Fagerberg, Dixon (The Accounting Review, 1954)
The article focuses on personal accounting. The principles, procedures and mechanics involved in accounting for individuals are basically the same as in business accounting. Their immediate objective, the preparation of meaningful financial and operating statements, is also the same. In pointing up the financial benefits to be derived from personal accounting, attention will therefore be centered on the personal financial statements as instruments for reflecting the underlying economics of an individual's affairs. To be of the utmost benefit, an individual's accounts should therefore be designed to produce financial statements that will clearly portray net results in terms of basic factors which includes earning power, saving power, and investment sagacity. The sources of personal earnings are practically unlimited and vary with each individual's land, labor, capital and enterprise. A detailed operating statement of the principal source of business or professional income is essential. Since a successful man's holdings will normally expand year by year, this supplementary investment income is of constantly increasing importance and for that reason the rate of return on his earning assets should be emphasized in his statements of earnings.